Discrete mathematics with applications - Epp, Susanna S (Cengage learning, 2020)
Discrete mathematics with applications / Epp, Susanna S.. -- Delhi: Cengage learning, 2020 511.3 Ep64e5 5th ed No. of Copies : 1